Valori e identità nell’Unione europea: un nuovo cleavage attraversa l’Europa? - Marchetti, Maria Cristina (Studi Politici, 2023)
The issue of European identity has been a major aspect of the debate on the integration process since the late 1990s. The paper aims to stress some peculiarities and contradictions, starting with the basic idea that European identity, like national one, is a collective identity. Through the reconstruction of some salient passages, the paper focuses on the following aspects: the contribution of European institutions to the construction of a common identity; Article 2 of the Lisbon Treaty and the “European Way of Life”. Finally, the paper aims to analyse the controversial way in which European identity is conceived today, identifying a new cleavage, which opposes European Union to Europe.